PENDEKATAN HOLISTIK INTEGRATIF DALAM PEMBELAJARAN PAI (STUDI IMPLEMENTASI DI SMA NEGERI 4 PURWOKERTO) - M. Slamet Yahya; Dede Wahyu Setyadi; Yusuf, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the fact that educational institutions in Indonesia, especially schools, are still facing problems with the character of students. One of the factors causing this problem is that educational institutions have not yet fulfilled the maximum level of integrative holistic teaching to students. Education in Indonesia has lost character values ​​and still focuses on mastering knowledge and lacks improvement in student characteristics. Education should provide holistic enlightenment to students to form individuals who are not only intellectually intelligent, but also have good moral, spiritual and social abilities. The research was carried out as a field research type, namely explaining events that took place in the implementation of holistic, integrative education in PAI learning at SMA Negeri 4 Purwokerto as the research object. The research uses qualitative methods with data collection techniques through observation, interviews and documentation which are analyzed using triangulation techniques. From the results of this research, it was found that the integrative holistic education paradigm understood at SMA Negeri 4 Purwokerto is an approach that combines various aspects of student development as a whole, including intellectual, emotional, social, physical and spiritual aspects. Integrative holistic education is implemented at Ngeri 4 Purwokerto High School, one of which is Islamic Education learning which is realized using the principles of mutual influence, namely: connectedness, inclusion and balance.